Effect of covalently functionalized Indian bentonite clay on thermal, mechanical strength and morphology structure of extrusion/injection-molded nylon 6 composites - Shanmugam, Kumaresan; Rokade, Dhammaraj S.; Ingole, Pravin G.; Pol, Harshawardhan V.; Arunachalam, Saravanakumar; Bajaj, Hari C. (Polymers for Advanced Technologies, 2024)
The research and development of functional polymer composites and their production have posed significant challenges, particularly in creating high mechanical strength and thermal stability composites. In this study, we utilized a micro corotation extruder and injection molding to produce covalently functionalized Indian bentonite clay-nylon 6 high-strength nanocomposites. For comparison, two different amines, 3-aminopropyl trimethoxysilane and N-[3-(trimethoxysilyl) propyl] ethylene di-amine, were used to functionalize bentonite clay. Additionally, 3% and 5% less amino clay filler was added in the nanocomposite to manufacture the polymer composite. Analytical techniques such as Powder X-Ray Diffraction, Fourier transform infrared, thermal gravimetric analysis, and Brunauer-Emmett-Teller surface area were used to characterize the molecular orientation of amine functionalization on clay minerals. Wide-angle X-ray diffraction, atomic force microscopy, and transmission electron microscope were used to characterize the nylon 6 intercalated in amino clay nanocomposite and the polymer structure morphology. Thermogravimetric analysis and differential scanning calorimetry were used to investigate the crystalline thermal behavior of clay-nylon 6 composites. From the results, it was observed that the composition containing 5 wt.% amino clay demonstrated a significant improvement in tensile strength when compared with the composition containing 3 wt.% amino clay. The mechanical strength and the thermal behavior showed a significant improvement of similar to 200% for 5% amino clay-nylon 6 nanocomposite.
Keywords: amine-functionalized clay; bentonite clay; melt intercalation; Nanocomposite; nylon 6; thermal and mechanical properties